2018
DOI: 10.21037/jtd.2018.07.119
|View full text |Cite
|
Sign up to set email alerts
|

Role of animal models for percutaneous atrial septal defect closure

Abstract: As for any preclinical development of new implantable device, bench testing has been followed by experimental studies on large animal models for the development of atrial septal defect closure devices. Various models have been used according to studied species (porcine, ovine or canine model) and whether the septal defect was percutaneously or surgically created. Animal models of percutaneous atrial septal defect closure aim to assess the healing process and device endothelialisation, as well as the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The volume of flow across a fenestration is affected by pressure gradient, viscosity of the blood, and body surface area among others. We propose that using Poiseuille’s law (see Appendix ) allows us to quantify the volume of blood flowing through the device . The relative viscosity of blood with a hematocrit of 40 to 45 is between 2.5 and 4, we used 3 as our viscosity at 37°C and hematocrit of 45.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The volume of flow across a fenestration is affected by pressure gradient, viscosity of the blood, and body surface area among others. We propose that using Poiseuille’s law (see Appendix ) allows us to quantify the volume of blood flowing through the device . The relative viscosity of blood with a hematocrit of 40 to 45 is between 2.5 and 4, we used 3 as our viscosity at 37°C and hematocrit of 45.…”
Section: Discussionmentioning
confidence: 99%
“…Pigs have been used for many years as models for medical research and particularly for ASD research. 7 Despite this, there are significant differences between porcine and human atrial septal geometry and structure. It is disappointing but not surprising, therefore, that one animal showed complete obliteration of the orifice of the AFR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 6‐month duration was decided on the basis of the results of a small population of animal experiments that showed that the devices were sufficiently neo‐endothelialized after 3 to 6 months. 23 , 24 , 25 To date, neo‐endothelialization has not been assessed in vivo in humans, and the evidence to support the appropriate treatment duration is inadequate. Only limited numbers of autopsy cases and device extraction cases demonstrated the extent of neo‐endothelialization of closure devices in humans.…”
mentioning
confidence: 99%